Myc-induced proliferation and transformation require Akt-mediated phosphorylation of FoxO proteins - Bouchard, Caroline (2004)
Myc synergizes with Ras and PI3-kinase in cell transformation, yet the molecular basis for this behavior is poorly understood. We now show that Myc recruits TFIIH, P-TEFb and Mediator to the cyclin D2 and other target promoters, while the PI3-kinase pathway controls formation of the preinitiation complex and loading of RNA polymerase II. The PI3-kinase pathway involves Akt-mediated phosphorylation of FoxO transcription factors. In a nonphosphorylated state, FoxO factors inhibit induction of multiple Myc target genes, Myc-induced cell proliferation and transformation by Myc and Ras. Abrogation of FoxO function enables Myc to activate target genes in the absence of PI3-kinase activity and to induce foci formation in primary cells in the absence of oncogenic Ras. We suggest that the cooperativity between Myc and Ras is at least in part due to the fact that Myc and FoxO proteins control distinct steps in the activation of an overlapping set of critical target genes.